2008
DOI: 10.1111/j.1440-1746.2008.05388.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased oxidation susceptibility of plasma low density lipoproteins in patients with Gilbert's syndrome

Abstract: It is suggested that the chronic hyperbilirubinemia leading to a lag-phase prolongation in LDL oxidation and a decrease in LDL oxidation may be reason for the low percentage of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…As an antioxidant, it has been shown to suppress the oxidation of lipids and lipoproteins, especially LDL cholesterol (5 ), and to be directly related to the total serum antioxidant capacity in humans (4 ). Recent studies indicate that the lipophilic bilirubin is more effective at protecting lipids from oxidation than the water-soluble antioxidants such as glutathione, which primarily protect proteins from oxidation (6 ). Deletion of heme oxygenase-2, which produces biliverdin, in mice was also found to result in greater lipid oxidation than protein oxidation, whereas the reverse was found for glutathione.…”
Section: Biological Properties Of Bilirubinmentioning
confidence: 99%
“…As an antioxidant, it has been shown to suppress the oxidation of lipids and lipoproteins, especially LDL cholesterol (5 ), and to be directly related to the total serum antioxidant capacity in humans (4 ). Recent studies indicate that the lipophilic bilirubin is more effective at protecting lipids from oxidation than the water-soluble antioxidants such as glutathione, which primarily protect proteins from oxidation (6 ). Deletion of heme oxygenase-2, which produces biliverdin, in mice was also found to result in greater lipid oxidation than protein oxidation, whereas the reverse was found for glutathione.…”
Section: Biological Properties Of Bilirubinmentioning
confidence: 99%
“…The protective effect of increased levels of bilirubin against atherosclerotic heart disease has been reported in many studies (17,18). Bilirubin is known to be a potent antioxidant that decreases lipid peroxidation and the chronic inflammation process (37). Thus, it is known to possess a cardiovascular protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that serum bilirubin level is inversely related to insulin resistance, serum insulin, triglyceride, systolic blood pressure, apolipoprotein B and obesity 53,83,84 . Even though the incidence of cholelithiasis in GS patients has been reported to be high, this increase is more prominent in concomitant conditions like cystic fibrosis, hereditary spherocytosis and sickle cell anemia [85][86][87] .…”
Section: Gs and Other Metabolic Conditionsmentioning
confidence: 99%
“…In patients with GS the low levels of LDL and CRP indicate low oxidative stress, strong capacity of antioxidation and low inflammation process. Indeed, previous studies have shown indirect bilirubin to be protective against lipid peroxidation and as a remover of peroxide radicals 52,53 .…”
Section: Gs Reduces the Risk Of Heart Diseasementioning
confidence: 99%